Constitutional amendments’ theory and troubles at supranational level: Constitutional change in the EU from the perspective of Richard Albert’s analysis - Fasone, Cristina (Revista de Investigações Constitucionais, 2020)
Richard Albert’s book offers a crucial systematization of constitutional amendments, their forms, procedures and scope. In doing so, it provides important insights on the theory and the practice of constitutional amendment design, the difficulty they face and the varieties of unamendability, amongst other things. This contribution seeks to apply Richard Albert’s analysis to the case of the European Union, where the existence of a fully-fledged Constitution has long been contested. It claims that this analytical framework can help to better understand the functioning of EU “constitutional amendments”, i.e. Treaty revisions, and their limits, in a context where they have remained substantially understudied.